9(1x-4)+9=4x+5(-5+1x

Simple and best practice solution for 9(1x-4)+9=4x+5(-5+1x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(1x-4)+9=4x+5(-5+1x equation:



9(1x-4)+9=4x+5(-5+1x
We move all terms to the left:
9(1x-4)+9-(4x+5(-5+1x)=0
We add all the numbers together, and all the variables
9(x-4)-(4x+5(x-5)+9=0
We multiply parentheses
9x-(4x+5(x-5)+9-36=0

See similar equations:

| -117=-3(7-8x) | | 2/5m=7 | | 7/5x-12=16 | | 3.7x+10=1.7x+20 | | 4=-2(x-3# | | 3/4=x=9 | | 3.x+10=1.7x+20 | | U^-3u=4 | | 2(3x-5)=-4(x+5) | | 3/5x-1/10x=x-17/2 | | -x+8+3=3 | | 6x+7=2x+59+2x | | -15=-7+3p-7p | | 7=x-12.2 | | 3x+2=30-x | | 87+2x=6 | | 11=x+6/x | | 4y/y+1=9-4/y+1 | | 8^5x+3=(1/64)^-2/3. | | -52=-4(4+3n) | | (x-11)/8=-3 | | 6x-3-2x=27 | | x-11/8=-3 | | 3(4n-2)=2n+12 | | (8x+51)=9 | | -38=-16-3/4x-10 | | 3000/(x-5)=20 | | 3p+2=28 | | 12=–4+2g | | 4x/4=1/1024/4 | | 5x-40+x-8=180 | | 6(n+6)=-30 |

Equations solver categories